Statistics in society: The arithmetic of politics - Dorling, D; Simpson, S (Arnold Publishers, 1998)
A collection of 47 papers edited by Danny Dorling and Stephen Simpson, published in 1999 by Arnold, reprinted in 2000 (and in Japanese in 2003). The claim of the book is that statistics are pervasive and powerful, but often misleading or misunderstood, no more so than when they concern society. The book presents a series of case studies are presented with the goal of showing specifically how statistics are used throughout society. It demystifies statistical reports and helps the reader become a more critical consumer of statistics and a more skilled user of statistical methods.